2011
DOI: 10.1007/s11418-011-0541-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting podophyllotoxin yield in the ex situ grown Podophyllum hexandrum, an endangered alpine native of the western Himalayas

Abstract: This study reports an appreciable yield of podophyllotoxin (PDT) in P. hexandrum plants grown ex situ under polyhouse conditions of a temperate locale. The PDT content of below-ground parts was affected by both plant age and growth period. However, only the effect of plant age on PDT content was significant. Thus, the highest amounts of PDT were recorded in the below-ground parts of 2-year-old plants harvested during the late-growth period (LGP). High total soluble sugars in the below-ground parts during the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This study conclusively demonstrated a positive correlation between podophyllotoxin content and an increase in the altitude (Nadeem et al, 2007). A recent study by Kushwaha et al (2011) also demonstrated the possibility of increasing podophyllotoxin yield in P. hexandrum plants when grown ex situ under polyhouse conditions of a temperate locale.…”
Section: Adaptive Response and Genetic Diversitysupporting
confidence: 77%
“…This study conclusively demonstrated a positive correlation between podophyllotoxin content and an increase in the altitude (Nadeem et al, 2007). A recent study by Kushwaha et al (2011) also demonstrated the possibility of increasing podophyllotoxin yield in P. hexandrum plants when grown ex situ under polyhouse conditions of a temperate locale.…”
Section: Adaptive Response and Genetic Diversitysupporting
confidence: 77%
“…Podophyllotoxin content in P. hexandrum rhizome is known to vary from 4% to 10% in reference to age, altitude, net photosynthetic rate, stomatal conductance, carbon uptake and number of leaves [49-52]. Green calli were found to have 40–50 μg/g podophyllotoxin which were used to generate cell suspension culture.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the natural source of podophyllotoxin is primarily derived from S. hexandrum and some other Epipodophyllaceae plants 3,14 .S. hexandrum The growth of S. hexandrum is closely associated with various ecological factors such as altitude, temperature, and rainfall 15,16 . It is typically found in remote and high-altitude regions that are characterized by cold temperatures, including Tibet, Yunnan, Sichuan, and Qinghai provinces in China 17 .…”
Section: Introductionmentioning
confidence: 99%